2023
DOI: 10.1182/bloodadvances.2022007947
|View full text |Cite
|
Sign up to set email alerts
|

Clinicogenomic associations in childhood Langerhans cell histiocytosis: an international cohort study

Abstract: Langerhans cell histiocytosis (LCH) is a rare neoplastic disorder caused by somatic genetic alterations in hematopoietic precursor cells differentiating into CD1a+/CD207+ histiocytes. LCH clinical manifestation is highly heterogeneous. BRAF and MAP2K1 mutations account for approximately 80% of genetic driver alterations in neoplastic LCH-cells. However, their clinical associations remain incompletely understood. Here, we present an international clinicogenomic study of childhood LCH, investigating 377 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 86 publications
5
25
0
1
Order By: Relevance
“…In the present study, BRAF V600E was found in 45.1% of all histiocytoses and in 50.3% of childhood LCH. This result is in accordance with previously published findings showing BRAF V600E in 19%–67.6% of pediatric LCH 3–6 . In four children with LCH in the current study, we observed more complex alterations (small deletion/duplication) around codon V600 (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, BRAF V600E was found in 45.1% of all histiocytoses and in 50.3% of childhood LCH. This result is in accordance with previously published findings showing BRAF V600E in 19%–67.6% of pediatric LCH 3–6 . In four children with LCH in the current study, we observed more complex alterations (small deletion/duplication) around codon V600 (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we identified MAP2K1 alterations in 20% of RDD cases and in one patient with JXG. Previous publications have reported MAP2K1 mutations in 11%–30% of pediatric LCH patients 5–7 and more rarely in other histiocytosis types 8,12,35,36 . Because non‐ BRAF V600E ‐mutated LCH cases constitute half of our LCH cohort, we can estimate that MAP2K1 mutations are found in 21% of childhood LCH, in accordance with previously published data.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations